2018
DOI: 10.1177/1066896918800812
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM Immunopositivity in Anaplastic Supratentorial Ependymomas: Correlation With Clinical and Histological Parameters

Abstract: Supratentorial ependymomas (ST EPNs) are molecularly characterized, of which the RELA fusion positive tumors are the most common and aggressive subgroup. Moreover, histologically, anaplastic ST EPN (ST-AE) often mimic other central nervous system primary high-grade tumors resulting in a diagnostic dilemma. We aimed to study a cohort of ST-AE; evaluate the expression of two RELA fusion-associated markers-L1CAM and p65 (NF-κB); and correlate their expression with clinical and histological parameters. Cases of ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Our study results showed that STEs often occurred in the second to fourth decades of life (mean age 32 years) and both genders were approximately equally affected; these are consistent with previous studies 15,16 . The tumors were most commonly located in the frontal lobe, with the temporal lobe and parietal lobe also frequently affected as reported in previous studies 17,18 . In the present study, the IEs shared similar age and gender characteristics with STEs, but were mostly located in the fourth ventricle, which could easily lead to obstructive hydrocephalus.…”
Section: Discussionsupporting
confidence: 91%
“…Our study results showed that STEs often occurred in the second to fourth decades of life (mean age 32 years) and both genders were approximately equally affected; these are consistent with previous studies 15,16 . The tumors were most commonly located in the frontal lobe, with the temporal lobe and parietal lobe also frequently affected as reported in previous studies 17,18 . In the present study, the IEs shared similar age and gender characteristics with STEs, but were mostly located in the fourth ventricle, which could easily lead to obstructive hydrocephalus.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a ZFTA-RELA fusion was detected in a case primarily diagnosed as centrally located malignant peripheral nerve sheath tumor as well as in a tumor that histologically appeared as 'astroblastoma'. L1CAM, a characteristic histopathological marker for ST-EPN-RELA (23,24), and nuclear p65, the protein encoded by RELA, could be evaluated by immunohistochemistry (IHC) in a limited number of samples from cluster 2, 3 and 4 as well as in ZFTA-RELA-negative and ZFTA-RELA type 8 cases. Apart from one sample in cluster 2, all cases expressed L1CAM to different extents, demonstrating that L1CAM-expression is not restricted to tumors harboring canonical ZFTA-RELA fusions (Fig.…”
Section: St-epn With Alternative Fusions Show Distinct Transcription Profiles and Atypical Histologiesmentioning
confidence: 99%
“…The most recent molecular studies on ependymomas based on their updated classification are based on immunohistochemistry. Immunohistochemistry studies distinguished supratentorial ependymomas in the RELA-fusion-positive and the yes-associated protein 1 (YAP1)-fusion positive subgroups, the Neural cell adhesion molecule L1 (L1CAM) protein marking the first one and showing the most aggressive behavior [14]. CD44 was instead outlined as a biomarker of prognosis of posterior fossa ependymomas as well as being in association with abnormal activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) pathway (PI3K-Akt pathway) [15].…”
Section: Introductionmentioning
confidence: 99%